Perceived Organizational Support (POS) and Work Discipline on the Performance of Village Officials through Organizational Commitment as a Mediating Variable - Nuraini Nuraini; Mahmud Mahmud; Shoalihin Shoalihin (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the effects of Perceived Organizational Support (POS) and work discipline on the performance of village apparatus, specifically examining organizational commitment as a mediating variable. Research Method: A quantitative approach was employed, using a saturated sampling (census) of 54 village apparatus across the villages of Lune, Jambu, and Ranggo, Indonesia. Data were collected via questionnaires on a 5-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results and Discussion: POS significantly enhances both apparatus performance and organizational commitment. While work discipline strongly builds commitment, it has little effect on direct performance. Furthermore, organizational commitment fails to mediate the relationship between POS, work discipline, and performance. This indicates that psychological attachment alone cannot drive optimal productivity without practical, task-related support. Implications: Village governments must prioritize creating supportive work environments and technical capacity-building rather than relying solely on apparatus loyalty to improve public service. Future studies should employ mixed methods and incorporate broader variables, such as leadership and motivation. Originality: This study provides novel empirical evidence that contextualizes Social Exchange Theory within rural public bureaucracy, demonstrating that the mediating efficacy of organizational commitment is neither universal nor uniform in village governance.